Attribute based Access Control Scheme in Cloud Storage System - SeethaRamulu, Banoth; Balaji, H.; Suman, Bashetty (International Journal of Engineering and Technology, 2018)
Cloud Computing is an emerging technology now a days , where cloud is most preferable when there is data backup, storage and data distribution service with low cost. But cloud is semi honest in nature due to not reveled storage and security structure thus while storing and sharing cloud data , its suppose to honest and secured. When data owners outsource their data in secured manner system should assure the security, data integrity and confidentiality. Here we noticed secure access controlling is the prime objective for sensitive data management.in this regards we have been used ABE (Attribute based encryption) for the above objective. This paper concentrates on secure storage and sharing system.Â Â